ANALYSIS OF THE CAPER METHOD (BEGINNING READING) IN BASIC LITERATURE EDUCATION IN THE LEARNING HOUSE OF PERGULAAN VILLAGE - Dea Anggriani Arda; Ayu Iga Ardini; Dwi Ayu Chairinisa; Friska Indria Nora; Sudirman Sudirman (IKIP Siliwangi Bandung, 2023)
This research was conducted with the aim of analyzing the learning methods used for basic literacy learning at the Pergulaan Village Learning House, Sei Rampah District, Serdang Bedagai Regency. In this study, the method used is descriptive qualitative method. In collecting data, researchers used interview techniques with home learning educators and direct observation in the village of Pergulaan. The interviews conducted were unstructured interviews. After analyzing the learning at the learning house in the sugar village, the researchers found that the learning house in the sugar village used the Caper (Beginning Reading) method. The results obtained with this method are that children are more interested in learning because they don't feel bored and with the Caper method it can be seen the effectiveness of the learning process, namely from around 12 residents studying at this learning house one month after being taught using the Caper learning method (Beginning Reading) there are 5 learning residents who can read. This means that using the caper learning method is quite effective in improving the reading skills of the learning citizens.